Managing Cybersecurity Threats and Increasing Organizational Resilience - Trim, Peter R.J; Lee, Yang-Im (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Cybersecurity attacks are increasing in sophistication and intensity and are known to have a disruptive effect on organizations and society. This reprint contains a range of papers that address various issues relating to the problem, and insights are provided into how cybersecurity awareness can be increased and how organizations can be made less vulnerable to attacks. The solutions put forward will help staff to utilize technology better and devise methodological approaches that when operationalized, help defend the organization's networks and computer systems from cyber-attacks.